Reforma al artículo 93 de la ley del sistema nacional de contratación pública, respecto a la terminación de los contratos por mutuo acuerdo - Narváez Portillo, Favio Paúl (2015)
Throughout the existence of the human being, there has been various forms of agreements, which then of nominated contracts, ie as humanity is organized in social and economic aspects, because from there part the determination of putting special features for legal economic agreement. In early Neolithic about development time mentioned this so call "primitive trade", he was known as barter, this being a legal way to market products or goods to different people for the time required it as a priority need. As the exchanges of products were making between different people and distant place, to facilitate operations began to use certain items of small size but of significant value and easy to use. Among the articles used the same silver initially used to make useful everyday uses such as vases, cups, spoon was, etc. This metal was gradually losing its quality as raw material for personal items to be turning over time as the unit of abstract value, regardless of the values of a previously represented. That was how the money was born as a symbol of courage and form of contract for the procurement of the time, later were using other more abstract symbols, which shone through the purchase of products, so that paper money commonly called ticket. All these changes were emerging as necessary to facilitate commercial transactions between people and not by mere innovative tastes. The effects that caused all these forms and characters to recruit, led to rules in handling as it was generally recognized and official control. He also sought to be representative of actual values, ie, whether there was rules governing, or turn legislation to determine the agreements that you then they are conducted orally, where the conduct of paramount negotiation so to speak contract was put a quantitative meaning of the same value which the acquirer adhered. And for purposes of this, the contract was shaped in part to thereby establish the special peculiarities of integrity, it must contain and then the contractors may by mutual agreement and I deslindarlo the interests of each of them. Thus, the contract is us more than two partners or individual subjects agree to conduct an economic commercial transaction, which leads consent is immersed their ability to recruit and hire bans, the objects being the most important for contain the item if possible or lawful, of why performing this contract is part of the cause, and finally the form of financial approvals and approvals of legal solemnity to contain in one document. Our country has had in recent times legal transformations in terms of recruitment, and because the public sector in 2008, for the month of August, on a Monday 4 issued in its Official Gazette No. 395, Law organic National public Procurement System, with the end in all its processes, contractual party procurement by public entities and termination of these contracts with private or public entities, is their different ways of terminating them